Capacidade das organizações de formar e implementar estratégias: construção de artefato para avaliação - Nicolela, Rafael Teixeira (Universidade do Vale do Rio dos Sinos, 2017)
Strategy is a highly relevant topic for management, occupying a prominent place in academic research, and in the practices of organizations. It is also a complex theme: different perspectives, several schools of thought, some research focused on content and others in process, some research focusing on the formulation of strategies, others on their implementation. Perhaps due to this complexity, the failure rate with strategies is very high: estimates point to 60 to 70% of failures in strategic changes. The purpose of this research is to help companies understand their ability to propose and implement good strategies. Adopting a procedural approach, the research proposes an artifact to measure the capacity of the strategic process, with the belief that measuring this capability is the first step towards a plan for improvement. Through a qualitative and quantitative research, the work develops a maturity evaluation framework for the strategic process and applies it to a population of companies in Rio Grande do Sul of different industrial segments and different sizes. The initially proposed model is partially validated in a first test. The contribution of this research to the practical community is generally the recommendation of using process management methods to improve the capacity of the strategic process, and specifically the proposition of a model for maturity evaluation. We did not find any research with this intent.
Keywords: Estratégia; Processo estratégico; Capacidade do processo estratégico; Maturidade do processo estratégico; Gestão de processos; Strategy; Strategy process; Strategy process capability; Strategy process maturity; Process management; ACCNPQ::Ciências Sociais Aplicadas::Administração